361. A new therapy with 188Re for non-melanoma skin cancers. First experiences. (December 2018) - Zagni, F.; Lima, G.M.; Farina, A.; Castellucci, P.; Savoia, F.; Kirikova, A.; Wendler, T.; Fanti, S.; Marengo, M.
Abstract : Purpose: In the last few years, following on an initial concept developed by Cipriani et al., a new medical device has been certified in Europe for the therapy of basal and squamous cell carcinomas of the skin. Here we report our initial experience on technical and safety aspects. Materials and methods: The principle of operation is based on the application of a resin of 188 Re over a thin plastic film attached on the lesion. After appropriate treatment time, the plastic foil is safely removed and discarded. The device is all-in-one, as it allows the final formulation of the resin, the application of the compound and measurement of activity. Irradiation of the operators is minimal: the ampule of the resin is extracted from the shielded cabinet only for measurement in the dedicated activity meter, and for the application. The operators are protected by leaded aprons (against the 155-keV photons), and by plastic shields/glasses for the beta radiation. Size and depth of the lesion are determined by a Dermatologist and from biopsy, and used, together with the amount of activity effectively applied, as the input data in the code Varskin (RASSC, USA; v.5.3), to assess the treatment time. Results/Conclusion: The completeness of the device makes its clinical use relatively simple, after the necessary initial training. Operation is safe and completely painless for the patient. Proper timing in the application to patients is necessary, since multiple layers of the resin may be necessary to reach the wanted activity (the resin hardens in approximately 15 min). At the time of submitting this abstract we have treated 7 patients (activity range 700–1000 MBq applied for 30–120 min). While lesions' healing was observed, it's still not possible to draw sound clinical conclusions; meantime we are currently working on a MonteCarlo model to support dosimetry calculations with Varskin.